100% Fruit Juice and Dental Health: A Systematic Review of the Literature - Liska, DeAnn; Kelley, Michael; Mah, Eunice (Frontiers in Public Health, 2019)
Abstract Background: The objective of this systematic review was to assess the scope and breadth of publicly available prospective cohort and randomized controlled trial (RCT) literature on 100% fruit juice and dental caries or tooth erosion in humans. Methods: We performed a systematic search in MEDLINE/PubMed, EMBASE, and Web of Science for studies published from inception through May 2018, and the Cochrane Library databases for reports published through January 2018. Prospective cohort studies or RCTs conducted on dental health and 100% fruit juice and published in English were selected. No restrictions were set for age, sex, geographic location, or socioeconomic status. Results: Eight publications representing five independent prospective cohort studies and nine publications on nine RCTs were included. All prospective cohort studies were in children or adolescents, and all RCTs were in adults. Prospective cohort studies on tooth erosion found no association between juice intake and tooth erosion, while those on dental caries incidence reported either no association or an inverse association between 100% fruit juice intakes and dental caries incidence. RCTs on tooth erosion showed decreased microhardness, increased surface enamel loss, increased erosion depth, greater enamel softening, and/or increased pellicle layer with 100% fruit juice, and those on dental caries showed increased demineralization of enamel slabs with 100% fruit juice. Conclusions: The existing evidence on 100% fruit juice intake and caries and tooth erosion are not conclusive. Overall, prospective cohort studies in children and adolescents found no association between 100% fruit juice intake and tooth erosion or dental caries, but, RCT data in adults suggests that 100% fruit juice could contribute to tooth erosion and dental caries. The RCT data, however, were from small, short-term studies that utilized intra-oral devices generally devoid of normal plaque or saliva action, and generally employed conditions that are not reflective of normal juice consumption.